1986
DOI: 10.1007/bf01820642
|View full text |Cite
|
Sign up to set email alerts
|

The origin and evolution of the Menderes Massif, W-Turkey: A rubidium/strontium and oxygen isotope study

Abstract: Das Menderes Massiv ist ein alpinotypes Gebirge derWest-Tfirkei und besteht aus drei tektonisch-lithologischen Einheiten, die in den ,,Gneisskern, und in die ,,Schieferhfille,~ und ,,Marmorhfille,~ gegliedert werden. Diese Arbeit berichtet fiber Isotopenanalysen, die an einer metasediment/iren und migmatitischen Gesteinsserie yore Sfidrand (Typ A) und an einer metatonalitischen bis metagranitischen Gesteinsserie yore Nor&and des Menderes Massivs (Typ B) durchgefiihrt wurden.Die Rb-Sr-Gesamtgesteinsisochrone de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
0
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(104 citation statements)
references
References 30 publications
7
95
0
2
Order By: Relevance
“…The Menderes Massif is intensely sheared during hightemperature and medium-pressure (Barrovian) metamorphism (the so-called Main Menderes Metamorphism, or MMM [Akkök, 1983;Ashworth and Evirgen, 1984;Sengör et al, 1984;Satir and Friedrichsen, 1986;Bozkurt and Park, 1999;Whitney and Bozkurt, 2002;Sengün et al, 2006]. This MMM postdates a phase of HP metamorphism and eclogite formation in mafic pockets in the Pan-African orthogneisses Candan et al, 2001] and also postdates HP metamorphism [Régnier et al, 2007] under blueschist facies conditions Oberhänsli et al, 1998;Rimmelé et al, 2003b;Whitney et al, 2008] in the Paleozoic to Eocene sedimentary cover.…”
Section: Structure and Metamorphism Of The Menderes Massifmentioning
confidence: 99%
“…The Menderes Massif is intensely sheared during hightemperature and medium-pressure (Barrovian) metamorphism (the so-called Main Menderes Metamorphism, or MMM [Akkök, 1983;Ashworth and Evirgen, 1984;Sengör et al, 1984;Satir and Friedrichsen, 1986;Bozkurt and Park, 1999;Whitney and Bozkurt, 2002;Sengün et al, 2006]. This MMM postdates a phase of HP metamorphism and eclogite formation in mafic pockets in the Pan-African orthogneisses Candan et al, 2001] and also postdates HP metamorphism [Régnier et al, 2007] under blueschist facies conditions Oberhänsli et al, 1998;Rimmelé et al, 2003b;Whitney et al, 2008] in the Paleozoic to Eocene sedimentary cover.…”
Section: Structure and Metamorphism Of The Menderes Massifmentioning
confidence: 99%
“…This may have been responsible for the more alkaline (potassic) character of the volcanism in the eastern Aegean. It has been shown from isotopic studies (Stouraiti et al, 1998;Altherr et al, 1988;Satir et al, 1986) that the granitoids of the eastern Aegean have a higher proportion of enriched mantle component relative to the western arc magmatic rocks, as a result of this different tectonic regime. It is suggested that this is associated with a rather specific tectonic setting in the broad eastern Aegean area, including Kos-Samos-Patmos-Chios and Bodrum, in a zone extending broadly in a N S orientation, that is transverse to the modern volcanic arc.…”
Section: Discussionmentioning
confidence: 99%
“…Sr and Nd isotopic ratios obtained from the MCC vary from 0.71655 to 0.86800 and 0.51218 to 0.51283, respectively (Satır and Friedrichsen 1986;Ersoy et al 2012a;Çoban et al 2012), which are clearly distinct from the magmatic rocks in the region. Hence, even low-degree contamination of the parental magmas by rocks of the MCC would yield magmas with very high 87 Sr/ 86 Sr ratios.…”
Section: Crustal Contaminationmentioning
confidence: 97%